Distance and on-line learning as challenge to the modern world - Siusiuka, V.; Sergienko, M.; Kolokot, N.; Shevchenko, A.; Roslik, O.; Сюсюка, Володимир Григорович; Сергієнко, Марина Юріївна; Колокот, Наталя Григорівна; Шевченко, Анна Олександрівна; Рослік, Ольга Анатоліївна (Гродно, 2020)
Distance forms of work were used in State Medical University of Zaporizhzhia for many years; mainly it was related to upgrading of teacher’s skills. Owing to the quarantine within the territory of Ukraine in order to prevent distribution of acute respiratory disease – COVID 19 the introduction of distance educational methods became today’s need. All teachers and students have open access to MS Office 365 - the service of distance learning and MS Teams software.